Matrix disequilibrium in Alzheimer’s disease and conditions that increase Alzheimer’s disease risk - Amontree, Matthew; Deasy, Samantha; Turner, R. Scott; Conant, Katherine (Frontiers in Neuroscience, 2023)
Alzheimer’s Disease (AD) and related dementias were the seventh leading of death globally in 2019 (GBD 2019 Collaborators et al., 2021). Currently 42 million people live with AD and that number is expected to triple to 153 million people in 2050 (Nichols et al., 2022). Despite this expected increase in the prevalence of AD, we have yet to elucidate the causality of the neurodegeneration observed in AD and we lack effective therapeutics to combat the progressive neuronal loss. Throughout the past 30 years, several non-mutually exclusive hypotheses have arisen to explain the causative pathologies in AD: amyloid cascade, hyper-phosphorylated tau accumulation, cholinergic loss, chronic neuroinflammation, oxidative stress, and mitochondrial dysfunction. Published studies in this field have also focused on changes in neuronal extracellular matrix (ECM), which is critical to synaptic formation, function, and stability. Recent work also supports a role for ECM as an effector of neuronal population dynamics, including gamma oscillations which may be reduced in AD (Klein et al., 2016). Two of the greatest non-modifiable risk factors for development of AD (aside from autosomal dominant familial AD gene mutations) are aging and APOE status, and two of the greatest modifiable risk factors for AD and related dementias are untreated major depressive disorder (MDD) (Almeida et al., 2017) and obesity (Slomski, 2022). Indeed, the risk of developing AD doubles for every 5 years after ≥ 65 (Qiu et al., 2009), and the APOE4 allele increases AD risk in a dose dependent manner. Of relevance to ECM changes with AD risk factors, many studies have demonstrated increased CNS ECM with aging (Knuesel et al., 2009; Reed et al., 2018; Végh, et al., 2014), APOE4 status (Jackson et al., 2022; Keable et al., 2020; Tcw et al., 2022; Yamazaki et al., 2020), MDD and obesity (Alonge et al., 2022; Dingess et al., 2018, 2020; Reichelt et al., 2019, 2021).